The Natural Stone Market in the Context of Rapid Construction Development and Protection Areas of Major Groundwater Reservoirs (GZWP) - Łochańska, Dorota; Kubiszyn, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Over the last few years, the demand for stone raw materials has increased significantly. The stone industry is an unusual sector that combines domestic stone extraction with the global market. The stone market supported by the achievements of new technologies provides a processed product, which in consequence create great potential for development of this sector. What is more an intensification of the demand effect on raw stones can be initiated by the construction industry, which is one of the basic drivers of the country`s economy.
Keywords: dimension and crushed stones; building stone market; environmental conditions; protection areas of Major Groundwater Reservoirs; GZWP